When x = 2 3 + 5 i ,find the value of 2 x 3 + 2 x 2 − 7 x + 7 2 .
Note : i = − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There's a small typo in the first line where you have 2x^2-6x+(1) instead of 2x^2-6x+(17). You have the 17 in the next step just forgot it in that first line. Nice observation about forming that polynomial. What was your process in the construction of that polynomial? The first part using vieta's was clever but the x+4 factor seems pretty arbitrary although it ended up working out very nicely. I ended up just plugging in the value for x lol (I factored out the 2x^2 for my convenience in the calculation).
Log in to reply
thanks, corrected. we want the term with x 2 to be 2. it is easy to find x+4 to do that. since the answer is obvously real we can deduce that a -7 will come with the x. we expand to see good luck!
Since Brilliant's input here requires an integer, it stands to reason that we only need the real part. This is
4 3 3 − 3 ⋅ 3 ⋅ 5 2 + 2 3 2 − 5 2 − 2 7 ⋅ 3 + 7 2 = 4 − 1 9 8 + 2 − 1 6 − 2 2 1 + 7 2 = 4 .
There are more elegant solutions, of course. But they take at least at much time :) Here is my alternative solution that might satisfy the purists among you:
Up to complex conjugation, x is the unique root of a quadratic equation, and working backward in the famous quadratic formula we have a = 1 , b = 3 , b 2 − 4 a c = − 2 5 ∴ 4 a c = − 3 4 ∴ c = 8 2 1 , so that the equation is x 2 − 3 x + 8 2 1 = 0 ∴ 2 x 2 − 6 x + 1 7 = 0 . We can reduce the order of the given polynomial by subtracting out multiples of this: 2 x 3 + 2 x 2 − 7 x + 7 2 = ( x + 4 ) ( 2 x 2 − 6 x + 1 7 ) + 4 = 0 + 4 = 4 .
To me, the most obvious start is to try to factor the polynomial. It factors as ( 2 x 2 − 7 ) ( x + 1 ) + 7 9 . Surprisingly enough, you get nice numbers when you expand - we end up with ( 1 5 ) ( 5 / 2 ) ( i + 1 ) ( i − 1 ) + 7 9 after plugging and chugging, which gives us 2 x 3 + 2 x 2 − 7 x + 7 2 = 4 .
Problem Loading...
Note Loading...
Set Loading...
x is a root of 2 ( x − 2 3 + 5 i ) ( x − 2 3 − 5 i ) = 2 x 2 − 6 x + 1 7 = 0 this is easy to expand because we can just sum and multiply by vietas. now, we mulyiply by (x+4) ( 2 x 2 − 6 x + 1 7 ) ( x + 4 ) = 2 x 3 + 2 x 2 − 7 x + 6 8 = 0 add 4 to both sides 2 x 3 + 2 x 2 − 7 x + 7 2 = 4